Gender Participation in Economic Activities and Decision Making in Keffi Area of Nigeria - Ibrahim, Hassan Ishaq; Saingbe , Napoleon Danbeki; Abdulkadir , Zubairu Ajiya (Asian Journal of Agriculture and Rural Development, 2012)
The study assessed gender participation and decision making role in economic activities using data collected from 120 respondents. The results revealed that female participation was frequent in crop post-harvest activities and poultry management while male participation was frequent in crop pre-harvest operations only. Female respondents participated occasionally in home gardening, goat rearing, hair dressing and food processing. Educational level, years of experience, personal income and credit obtained significantly influenced the level of gender participation in economic activities. The Males always made decisions on selection of crop variety, spending money, saving money, buying of necessities, and children’s education, while females always made decision on types of food for home consumption only. Age and income of respondents were the significant factors that influenced the level of gender involvement in decision making. Provision of credit facilities, sensitization on the importance of women involvement in decision making and mobilization of farmers to form co-operative societies are necessary impetus for improving women participation in economic activities and decision making.